2016
DOI: 10.1002/ehf2.12113
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine induced cardiomyopathy: a case of multiple hit cardiotoxicity

Abstract: Gemcitabine is a commonly used antineoplastic agent used to treat a variety of cancers with rarely reported cardiac side effects. We describe a case of a 67‐year‐old woman with follicular lymphoma who experienced a rarely reported side effect of gemcitabine: cardiomyopathy. This case highlights a multiple hit mechanism of myocyte damage that may occur following the use of multiple cardio‐toxic agents despite their administration in doses not associated with cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Several of the canonical anti-cancer drugs assayed in this study showed greater toxicity against HeLa cells than did the NSAIDs. Although the IC 50 values were lower against 3T3 or HFF1 fibroblasts or MCF-10A breast epithelium cells, all of the chemotherapy drugs have shown significantly greater cardiotoxicity [ 42 , 66 , 67 , 68 , 69 ] than the NSAIDs which are presumably less harmful [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several of the canonical anti-cancer drugs assayed in this study showed greater toxicity against HeLa cells than did the NSAIDs. Although the IC 50 values were lower against 3T3 or HFF1 fibroblasts or MCF-10A breast epithelium cells, all of the chemotherapy drugs have shown significantly greater cardiotoxicity [ 42 , 66 , 67 , 68 , 69 ] than the NSAIDs which are presumably less harmful [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that specific concomitant intake of anticancer drugs on top of gemcitabine were more likely to be associated with different type of cardiotoxicities such as platins with MI, HER-2 blockers with HF, and immune checkpoint inhibitors with pericardial disorders. Indeed, these drugs are known to induce these conditions and the hypothesis of toxic synergy or multiple hit mechanisms with these combinations is likely [ 18 , 45 , 46 ]. Overall, the co-administration of drugs that can induce CV-ADR should strengthen the surveillance of high-risk cardiovascular patients receiving combination of such agents.…”
Section: Discussionmentioning
confidence: 99%
“…Few cases are reported in the literature about cardiac dysfunction caused by isolated treatment with gemcitabine [ 1 ]. Some cases reported cardiomyopathy induced by gemcitabine after treatment with cardiotoxic anticancer drugs such as anthracyclines [ 8 ]. Generally treatment with gemcitabine can cause supraventricular tachycardia including atrial fibrillation, especially after 18–24 h of infusion [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some cases reported cardiomyopathy induced by gemcitabine after treatment with cardiotoxic anticancer drugs such as anthracyclines [ 8 ]. Generally treatment with gemcitabine can cause supraventricular tachycardia including atrial fibrillation, especially after 18–24 h of infusion [ 8 ]. In addiction, several case reports have demonstrated acute myocardial infarction post-gemcitabine injection secondary to drug-induced vascular injury or endothelial damage [ 9 10 ].…”
Section: Discussionmentioning
confidence: 99%